Keragaan Komponen Hasil dan Keragaman Genotipe Ubi Jalar Lokal Papua - Paskalius Aprianto Merahabia; Yunita Demena; Amius Tabuni (Badan Penelitian dan Pengembangan Provinsi Papua Barat, 2022)
Papua is known to have a high genetic diversity of sweet potato. This study aims to obtain information on the performance of yield components and genotype diversity of local Papuan sweet potatoes. This research was carried out for ± 5 months, starting from March to August 2021 located at the Manggoapi Experimental Garden, University of Papua. The study used a Randomized Block Design (RAK) with 4 genotypes of Papuan sweet potato, namely, Bovendigoel-1, Bovendigoel-2, Bovendigoel-3 and bovendigoel-4. Data analysis includes Analysis of Variety, Principal Component Analysis, Cluster Analysis and Coefficient of Correlation. The results showed that the test genotype had a very significant and significant effect on the characters of tuber diameter, tuber length, number of tubers per plant, tuber weight per plant, number of economic tubers, economic tuber weight, number of tubers per mound, tuber weight per mound, sugar content ( brix). There is genetic diversity in 4 local Papuan sweet potato genotypes with a similarity coefficient of 0.17-0.62. There are two main components with a cumulative variance of 94.657%. There is a positive correlation between economic tuber weight and yield.